Synthesis and Characterization of Low Molecular Weight Irradiated Chitosan in Various Water Levels and Gamma-Ray Doses - Rosspertiwi, Reni; Yunus, Ade Lestari; Rahayu, Dien Puji; Nurlidar, Farah; Azizah, Yulyani Nur (Jurnal Kimia Valensi, 2024)
Chitosan is a biopolymer derived from marine animal shell waste that exhibits numerous pharmacological activities. However, its high molecular weight limits the application in various fields due to its low solubility. Therefore, this study aims to synthesize low molecular weight chitosan using varying water content and doses of gamma irradiation. To initiate chitosan degradation, H2O (5 and 10 mL) was added, followed by gamma ray irradiation at doses of 5 and 10 kGy. The Molecular Weight (MW) of degraded chitosan was determined using Gel Permeation Chromatography (GPC), while Fourier Transform Infrared Spectroscopy (FTIR) was used to characterize the functional groups and degree of deacetylation of chitosan. The study found that the molecular weight of irradiated chitosan decreased as the irradiation dose and H2O addition increased. The addition of 10 mL of water and gamma irradiation at a dose of 10 kGy has been found to reduce the molecular weight of chitosan to 118 kDa, with a high deacetylation degree of 86.78%. The FTIR analysis showed no significant changes in the functional groups, indicating that gamma irradiation did not affect the structure of chitosan.